Incidencia de los reactivos de base estructurada en el proceso de evaluación de aprendizajes de los niños de quinto año de educación general básica en el colegio de bachillerato técnico Simón Rodríguez, barrio Laigua de Simón Rodríguez, parroquia Aláquez, cantón Latacunga en el período lectivo 2014 – 2015 - Romero Lamar, Erika Raquel (2015)
The primary purpose of this research is the implementation of a methodological guide in order to structure items (reactives) with base structured in order to demonstrate students` learning outcomes from Technical of Bachillerato Simón Rodríguez High School, the guide must be feasible, safe reliable and subsequently allow updates according to needs in the institution, so an analysis of educational books was made that helps the methodological guide development, therefore improving education in the Cotopaxi province and in the country. A good grade means an increase in teachers and parents` degree of satisfaction, as well as for the institution, because deficiencies and poor academic performance will decrease, therefore the quality of education will increase. It is made from a bibliographic analysis of Structured Base Reactives. One proposes the procedure that the methodological guide must follow, and processing and structuring of items are explained. Finally, we will develop the methodological guide for High School Simón Rodríguez, all possible facilities to make this work with the required effectiveness, applied learning goals, assisting in the fulfillment of all proposed methodological guide are provided.